English Language Teachers’ Awareness and Practice of Digital Teaching - Tiwari, Hari Prasad (Fakultas Sastra - Universitas Muslim Indonesia, 2024)
Raising English language teachers' awareness and practice of digital teaching is essential for creating interactive, engaging, and effective learning environments that cater to the diverse needs and interests of students. This study aims to explore the digital teaching awareness of secondary level English teachers and the technology-driven activities implemented in their classrooms. Employing a qualitative approach within the narrative inquiry framework, data was gathered from 12 secondary level English teachers through semi-structured interviews, direct observations, and document analysis. The results reveal that secondary level English teachers in Nepal develop their digital teaching skills and knowledge by engaging in professional development programs, including workshops, seminars, and conferences, as well as through self-directed learning from online platforms like YouTube. Additionally, they enhance their digital teaching strategies by utilizing social media platforms such as Facebook, WhatsApp, and Instagram, along with web-based tools. These findings provide valuable insights and resources for English teachers, which can be applied in the classroom to promote interactive, technology-enhanced learning and teaching activities. Furthermore, the results can inform policymakers at educational institutions to ensure the efficacy of digital language learning practices.